2001
DOI: 10.1037/0022-006x.69.6.992
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the impact of child sexual abuse on women: The role of abuse severity, parental support, and coping strategies.

Abstract: Female Navy recruits (N = 5,226) completed surveys assessing history of childhood sexual abuse (CSA), childhood strategies for coping with CSA, childhood parental support, and current psychological adjustment. Both CSA and parental support independently predicted later adjustment. In analyses examining whether CSA victims' functioning was associated with CSA severity (indexed by 5 variables), parental support (indexed by 3 variables), and coping (constructive, self-destructive, and avoidant), the negative copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
113
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 56 publications
(124 reference statements)
14
113
1
4
Order By: Relevance
“…Use of self-destructive coping in response to CSA was positively associated with both dysfunctional sexual behavior and number of sex partners, and dysfunctional sexual behavior was positively associated with number of sex partners. This suggests that sexually abused women who initially cope with abuse in self-destructive ways may be prone to continued use of self-destructive strategies, such as engaging in dysfunctional sex- ^ Merrill et al (2001) documented increased use of adaptive as well as avoidant and self-destructive coping strategies among participants with more severe abuse. However, CSA severity and coping as predictors of sexual functioning and behavior have not been previously studied in this sample or in any other sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of self-destructive coping in response to CSA was positively associated with both dysfunctional sexual behavior and number of sex partners, and dysfunctional sexual behavior was positively associated with number of sex partners. This suggests that sexually abused women who initially cope with abuse in self-destructive ways may be prone to continued use of self-destructive strategies, such as engaging in dysfunctional sex- ^ Merrill et al (2001) documented increased use of adaptive as well as avoidant and self-destructive coping strategies among participants with more severe abuse. However, CSA severity and coping as predictors of sexual functioning and behavior have not been previously studied in this sample or in any other sample.…”
Section: Discussionmentioning
confidence: 99%
“…A modified version of the How I Deal With Things Scale (Burt & Katz, 1987) was used to assess coping (see Merrill et al, 2001, for information about scale modifications). Respondents who had experienced CSA were asked to rate the frequency (1 = rarely, 5 = usually) with which they used each of 30 coping strategies to deal with their childhood sexual experience(s) "in the weeks and months after it first occurred."…”
Section: Methodsmentioning
confidence: 99%
“…El modelo predominante para clasificar las estrategias empleadas en el afrontamiento del abuso es el de aproximación-evitación, según el cual, los pensamientos y/o acciones se pueden dirigir hacia una amenaza (aproximación) o a alejarse de ella (evitación) (Merrill, Thomsen, Sinclair, Gold y Milner, 2001). Prácticamente todos los estudios que han examinado el efecto de diferentes estrategias han encontrado una relación entre las estrategias de evitación (p.e., negación, distanciamiento, aislamiento social) y un peor ajuste psicológico tras el ASI (Cantón-Cortés y Cantón, 2010;Hébert, et al, 2006).…”
Section: Variables Cognitivas De La Víctimaunclassified
“…However, outcomes following the disclosure of CSA have been described as quite diverse (Hébert et al 2006a, b;Paolucci et al 2001) and empirical reports have identified factors associated with variability of outcomes. Some studies revealed that abuse-related characteristics such as the duration (chronic) and severity of acts (penetration), the perpetrator's identity (intra-familial perpetrator) as well as the use of coercion have been related to more detrimental outcomes (Hulme and Agrawal 2004;Merrill et al 2001). However, other studies have failed to identify a link between abuse-related variables and children's symptoms (Bal et al 2004 …”
Section: Introductionmentioning
confidence: 99%
“…The first study explored the psychological distress of more than 4 000 female navy-recruits (M age = 19.7 years-old), comparing those who reported CSA (N =1 134) to non-victims. Results revealed that a retrospective recall of maternal and paternal support during childhood predicted psychological distress in adult women (Merrill et al 2001). The second study involved 188 undergraduate women (including 44 victims of CSA; M age = 21 years-old) and revealed that the presence of paternal support among women who reported CSA predicted better selfesteem.…”
mentioning
confidence: 97%